(untitled) (Journal of Biomedical Investigation, 2011)
The study was designed to determine the serum levels of antioxidants, mineral levels, antioxidant enzymes and total antioxidant status in diabetic patients, and the control subjects. The plasma levels of antioxidants (albumin, uric acid, total antioxidant status) minerals (magnesium, zinc, selenium and copper) and antioxidant enzyme (superoxide dismutase, glutathione peroxidase and catalase) were estimated in diabetic and control subjects. In the diabetic patients, the mean fasting blood glucose (FBG)(9.374 ±1.166) mmol/L is significantly higher (P<0.005) when compared with the controls (4.81820.815) mmol/L. Antioxidants uric acid (6.506±1.522) mg/dl, zinc 112.234±18.125) ug/dl and selenium levels (18.0530±2.166) pg/dl were significantly higher (P<0.005) when compared with the control subjects (5.468±1.600) mg/d|, (90.923£14.519) pg/di and (17.080£2.157) pg/dl respectively. Conversely, magnesium level (306.870±56.803) pg/dl was significantly lower (P<0.005) when compared with the control subjects (342.085±67.409) pg/dl. Age of subjects correlated negatively with their serum selenium levels (r=-0.311). This study demonstrated the presence of oxidative stress in the diabetic patients as an expression of increased free radical production and diminished antioxidant defense. Appropriate supplementation of antioxidants and minerals in these patients will strengthen their immune system and reduce the adverse consequences of oxidative stress. Routine assessment is recommended.